The country risk in foreign direct investment: concept and categories of risks - Noemi Dans Rodríguez (Papeles de Europa, 2013)
The assessment of country risk in exports is based on the analysis of the capacity ofpayment and the eventual losses for the creditor. The country risk in foreign directinvestment is, instead, related to the events that can produce losses as aconsequence of breach of contracts, deprivation of property rights, damage to assetsor cessation of activities. Considering that characteristics of exports and foreigndirect investment are different, this paper presents an analysis of the concept and thescope of country risk in both operations in order to know which categories of risk areshared and which categories are specific.